Natural Radioactivity in Some Building Materials Originating from a High Background Radiation Area - A.A, Kinsara; E.I, Shabana; M.M.T, Qutub (International Journal for Innovation Education and Research, 2014)
Twenty four samples of building materials, collected from utilized quarries dispersed randomly in a high natural background radiation area, were analyzed for 226Ra, 232Th and 40K by γ-spectrometry. This area lies in Hail province, Saudi Arabia. The collected samples were fragmented granites, granite gravels with clays, sands and crushed black rocks (mafic metavolcanic rocks). The results showed that the highest activity concentrations were found in the fragmented granite materials and ranged from 144-207, 671-1058 and 964-1440 Bq/kg with average values of 194, 912 and 1320 Bq/kg for 226Ra, 232Th and 40K, respectively. The lowest activity concentrations were found in the black rock materials which ranged from 19-39, 47-125 and 212-306 Bq/kg with average values of 24, 82 and 255 Bq/kg for 226Ra, 232Th and 40K, respectively. The radioactivity levels in the other materials lie somewhere in between. Granites and clays exceeded the proposed hazard indices for the usage as building materials and should be restricted, whereas the sands and the crushed black rocks complied with these indices and can be used without restrictions.